Conflicts of interest among scientific foundations and societies in the field of childhood nutrition - Guadalupe Guzmán-Caro; Fernando J. García López; Miguel Ángel Royo-Bordonada (Elsevier, 2021)
Objective: To describe food-industry sponsorships of associations active in the field of childhood nutrition and obesity prevention in Spain in 2017-2018. Method: The associations were located at https://www.google.es/ using the words "society", "foundation" or "federation" in combination with the terms "nutrition", "obesity", "childhood", "paediatrics" and "diabetes". Sponsorship was defined as the declaration of funding received or the appearance of a food company logo on an association's website or in the programmes of its congresses or courses. The percentage of sponsored societies and its association with the existence of ethical codes was calculated using MS Excel. Results: 64% of the associations displayed some type of sponsorship, with this being most frequent among paediatric and nutrition societies, 83% and 80% respectively, and non-existent among public health societies. No association was found between the existence of an ethical code and sponsorship (odds ratio: 0.75; 95% confidence interval: 0.14-3.94). The leading corporate sponsors were Nestlé, Coca-Cola and Danone. Whereas the initiatives of sponsored societies were targeted at changing eating individual behaviours, those of unsponsored societies sought to promote changes in the food system and eating environments. Conclusions: Food industry sponsorship of foundations and scientific societies is very widespread in Spain, except among public health associations. Unlike sponsored associations, those unsponsored propose policies opposed by the food industry, which are aimed at improving the system and food and eating environments. Resumen: Objetivo: Describir el patrocinio de compañías que comercializan alimentos y bebidas no saludables a sociedades científicas y fundaciones relacionadas con la nutrición y la prevención de la obesidad infantil en España durante 2017- 2018. Método: Las sociedades y fundaciones fueron localizadas en w*ww.google.es/ usando las palabras clave «sociedad», «fundación» y «federación», combinadas con «nutrición», «obesidad», «infantil», «pediatría» y «diabetes». Se consideró como patrocinio la declaración de financiación o la presencia del logo de la compañía alimentaria en la página web de la asociación o de los programas de congresos o cursos. Se calculó el porcentaje de asociaciones patrocinadas y su asociación con la existencia de código ético usando MS Excel. Resultados: El 64% de las asociaciones recibieron algún patrocinio de compañías alimentarias, más frecuente en las sociedades de pediatría (83%) y nutrición (80%) e inexistente en las de salud pública. No se encontró asociación entre la existencia de código ético y patrocinio (odds ratio: 0,75; intervalo de confianza del 95%: 0,14-3,94). Las principales compañías patrocinadoras fueron Nestlé, Coca-Cola y Danone. Las iniciativas de las asociaciones patrocinadas se dirigían exclusivamente a cambiar los hábitos individuales, mientras que las sociedades no patrocinadas promovieron cambios en el sistema y el entorno alimentarios. Conclusiones: El patrocinio de las compañías alimentarias a asociaciones relacionadas con la nutrición y la prevención de la obesidad infantil es común en España, excepto entre las sociedades de salud pública. A diferencia de las sociedades patrocinadas, las no patrocinadas promueven políticas alimentarias dirigidas a modificar el sistema y el entorno alimentarios, a las que se opone la industria alimentaria.